Caracterização de uma cepa do gênero Brevundimonas multidroga resistente, isolada de um paciente na Unidade de Terapia Intensiva, usando sequenciamento completo do genoma - Soares, Gabriela Guerrera (Universidade Federal de São Carlos, 2023)
Brevundimonas species have been considered an opportunistic human pathogen that can cause invasive and severe infections in patients with underlying pathologies. In order to increase our knowledge about these pathogens, we conducted in-depth genomic and phenotypic characterization of a Brevundimonas strain isolated from cerebrospinal fluid of a patient admitted in a neonatal intensive care unit. The strain was identified as a member of the genus Brevundimonas based on VITEK-2 system results and 16S rDNA sequence. Whole genome sequencing assembly of Brevundimonas sp. showed a total length of 3,261,074 bp and a G+C content of 66.86%, similar to other species of the genus. Multilocus sequence analysis, Type (Strain) Genome Server, digital DNA-DNA hybridization, and Average Nucleotide Identity (ANI) analyses confirmed that the Brevundimonas sp. studied represents a distinct species, for which we propose the name Brevundimonas brasiliensis sp. nov. In silico analysis detected genes associated with phenotypic characterization, related to resistance to β-lactams (penP, blaTEM-16, blaBKC-1) and aminoglycosides (strA, strB, aac(6’)-Ib, aac(6’)-Il). We also found genes encoding the AcrAB efflux pump that confers resistance to a broad spectrum of antibiotics, including β-lactams, tetracycline, novobiocin and fluoroquinolones. Colistin resistance can be attributed to mutation in qseC (Ile283Leu) and in phoP (Arg81Cis). Double amino acid substitution in GyrA (S83L and D87H), and amino acid substitution in GyrB (Glu466-Leu) may be associated with quinolone resistance. The isolate presented many virulence genes related to biofilm formation, adhesion, invasion, secretion, and that can be relevant to its pathogenicity. Brevundimonas brasiliensis sp. nov. genome contained copies of putative T4SS-type ICEs; putative IME; Tn3-type, and IS3, IS6, IS5, and IS1380-type families, suggesting an important role in the development and dissemination of antibiotic resistance, and pathogenicity of the isolate. Our data can provide a basis for understanding genomic variability, antibiotic resistance, pathogenicity, and dissemination of these resistant strains.
Characterization of a multidrug resistant Brevundimonas Strain, isolated from a patient in the Intensive Care Unit, using whole genome sequencing
Keywords: Brevundimonas sp.; Multidroga resistência; Multidrug resistance; Sequenciamento genômico completo; Whole genome sequencing; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA MEDICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA